A qualitative investigation into the so-called ministry of deliverance - J. Janse van Rensburg (In die Skriflig, 2010)
Since the publication of the book“The occult debate” (Janse van Rensburg, 1999) it has become clear that epistemological views on occultism within the reformed tradition have drastically diverged. During the General Synod of the Dutch Reformed Church in 2007, the report of the Algemene Taakspan vir Leer en Aktuele Sake (ATLAS)on a ministry of deliverance denied the existence of the devil and claimed that it would be un-scientific to embark on an empirical research in this regard, because of the impossibility to verify information gathered in this manner. However, it is the hypothesis of this article that qualitative information could assist in attaining a clearer under-standing of the need for a ministry of deliverance. In this article the methodology of the qualitative research is explained and the narratives of participants are revealed. Thereafter the respon-ses of the participants are evaluated.